MENGEMBANGKAN LITERASI DIGITAL DAN NUMERASI SISWA SMA MELALUI CMI AGENT - Nita Delima; Dianne Amor Kusuma; Jaja Jaja (IKIP Siliwangi, 2023)
The Covid-19 pandemic has had a significant impact on learning loss for students' literacy and numeracy skills. The comprehensive mathematics instruction (CMI) model has been transformed into a digital teaching material that can support interactive hybrid learning. The result of this transformation is named CMI Agent which is a learning management system (LMS) based platform arranged in the form of a quiz following the CMI model syntax. This study aims to analyze the advantages of CMI Agent in developing students' numeracy literacy and digital literacy. This research is a descriptive research with a survey method. Based on the studies that have been carried out, it is concluded that CMI Agent can support the development of students' numeracy literacy and digital literacy.